Embryo maturation, dormancy and seed storage behaviour of Gymnacranthera canarica (King) Warb., a threatened endemic tree species of Southern Western Ghats - Anusha, S.; Anilkumar, C.; Gangaprasad, A. (Current Botany, 2023)
Gymnacranthera canarica is a severely endangered endemic tree species found in the Myristica swamps of the Southern Western Ghats. Seed storage behaviour is an essential factor to consider when developing effective conservation methods for plant genetic resources whose ex-situ preservation is unclear. The seed storage behaviour, seed dormancy state, dormancy breaking treatments, germination, and phytohormonal analysis of G. canarica were explored in this work. G. canarica seed moisture at shedding was 28.86%, germinated to 34% at 25ºC, and had a low germination rate in natural conditions. Germination was considerably aided by Gibberellic acid pretreatment and drying stratification. G. canarica seeds may have non-deep simple morphophysiological dormancy, as evidenced by the fact that their embryos grew at temperatures between 20 and 25ºC (MPD). Seeds can be stored for up to 60 days at 20ºC after being desiccated to 19.37% suggest that G. canarica seeds are recalcitrant, with non-deep simple morphophysiological dormancy, and that seed pretreatment with Gibberellic acid prior to germination could be a viable approach for mass propagation and long term ex-situ conservation could be the potential storage of this critically endangered species.